Clear cell stromal tumor of the lung with multinucleated giant cells: a report of a case with YAP1-TFE3 fusion - Radek Jakša; Ivana Stružinská; Michaela Kendall Bártů; Stanislav Trča; Radoslav Matěj; Pavel Dundr (BMC, 2023)
Abstract Background Clear cell (hemangioblastoma-like) stromal tumor of the lung (CCSTL) is a rare pulmonary neoplasm. Recently, 9 cases of CCSTL harboring the YAP1-TFE3 gene fusion have been described, and it has been suggested that this aberration could be a characteristic feature of this tumor. Case presentation We here report another case of CCSTL in a 57-year-old male, which presented as a solitary lung nodule 45 mm in the greatest dimension. Microscopically, the tumor consisted of epithelioid to spindled cells with mild-to-moderate nuclear atypia, finely granular or vesicular chromatin, and small nucleoli. Nuclear indentations were a common finding. There were up to 3 mitoses per 10 HPF. The cytoplasm was slightly eosinophilic or clear. Scattered non-tumor large multinucleated cells were present. Immunohistochemically, the tumor cells showed diffuse positivity for TFE3, CD10, vimentin, and IFITM1. Other markers examined were negative, and the expression of lineage-specific markers was not found. NGS analysis revealed a fusion transcript of the YAP1 and TFE3 genes, and a pathogenic variant of the MUTYH gene. Conclusion Our finding supports the recent data suggesting that CCSTL represents a distinct entity characterized by the recurrent YAP1-TFE3 fusion.